2013
DOI: 10.1118/1.4814319
|View full text |Cite
|
Sign up to set email alerts
|

SU‐E‐J‐107: SEMAC MRI Metal Artifact Reduction Technique for Radiotherapy Planning Using CT/MRI Fusion

Abstract: Purpose: To assess the utility of SEMAC MRI metal artifact reduction technique for radiotherapy (RT) planning using CT/MRI fusion in patients with spine stabilisation devices. Methods: Conventional MRI spin‐echo (SE) sequences used for spinal cord delineation and radiotherapy planning in the spine were compared with a prototype implementation of Slice Encoding for Metal Artifact Correction (SEMAC) (WARP works‐in‐progress software package, Siemens Healthcare, Erlangen, Germany). Sequences were first optimised a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In some cases spinal metastases are stabilised with the use of metallic fixation devices, which degrade image quality of MR and CT examinations (FIGURE 11 spine+metal). For lesions located in the vicinity of metallic implants, it may be advantageous to employ MR techniques for metal artifact reduction (Panek et al, 2013). Although the degree of confidence in the CT-MR fusion increases as the artifacts are restricted to a smaller volume, further work is required to validate this approach and quantify its benefits.…”
Section: Applications Current Status and Future Perspectivesmentioning
confidence: 99%
“…In some cases spinal metastases are stabilised with the use of metallic fixation devices, which degrade image quality of MR and CT examinations (FIGURE 11 spine+metal). For lesions located in the vicinity of metallic implants, it may be advantageous to employ MR techniques for metal artifact reduction (Panek et al, 2013). Although the degree of confidence in the CT-MR fusion increases as the artifacts are restricted to a smaller volume, further work is required to validate this approach and quantify its benefits.…”
Section: Applications Current Status and Future Perspectivesmentioning
confidence: 99%
“…In contrast to diagnostic radiology, reports on the use of metal artifact reduction in radiotherapy planning are limited. Panek et al presented the preliminary results of SEMAC in the use of two radiotherapy patients with spine stabilization devices in 2013 (Panek et al 2013). Metal artifact volumes were reduced on average by 43%.…”
Section: Introductionmentioning
confidence: 99%
“…Initial experiments on test objects suggested that a number of 4 to 6 SEMAC slice-encoding steps [11] produced significant reduction in signal loss, in agreement with other reported studies [17] . However, we found necessary to reduce the number of averages and to increase the echo-train length in order to keep data acquisition within 5–6 min [18] . The reduction in averages is compensated by the gain in signal due to the SEMAC encoding, keeping the signal-to-noise ratio (SNR) of the image at an acceptable level.…”
Section: Methodsmentioning
confidence: 99%